Mindful Mobility in Bali: How Walking Experiences Shapes Sense of Place - Kezia Imanuella Tarigan; Ni Ketut Wiwiek Agustina; Ni Putu Evi Wijayanti (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2026)
TThis study examines how tourists develop a sense of place through guided walking tours in Bali’s cultural environments. Using Jorgensen and Stedman’s framework of place identity, place attachment, and place dependence, the research explores the psychological and emotional processes through which tourists construct meaning during their visits. An Interpretative Phenomenological Analysis (IPA) was conducted with six participants who recently joined walking tours. The analysis reveals three key experiential outcomes: (1) enhanced self-awareness and identity reflection, (2) emotional and well being-oriented benefits facilitated by mindful engagement with local spaces, and (3) functional dependence on walking as a mode of accessing authentic cultural experiences. These findings show that short-term walking tours can generate meaningful place-based connections, challenging assumptions that sense of place requires long-term immersion. The study contributes to sense of place theory by highlighting the role of embodied mobility in shaping tourist experiences and extends slow tourism scholarship by demonstrating how walking supports mindful, culturally grounded forms of engagement. Practically, the findings provide insights for developing sustainable, community-oriented walking tour products that promote cultural authenticity and visitor well being.